2019
DOI: 10.1017/wet.2019.48
|View full text |Cite
|
Sign up to set email alerts
|

Herbicide options for glyphosate-resistant kochia (Bassia scoparia) management in the Great Plains

Abstract: Kochia is one of the most problematic weeds in the United States. Field studies were conducted in five states (Wyoming, Colorado, Kansas, Nebraska, and South Dakota) over 2 yr (2010 and 2011) to evaluate kochia control with selected herbicides registered in five common crop scenarios: winter wheat, fallow, corn, soybean, and sugar beet to provide insight for diversifying kochia management in crop rotations. Kochia control varied by experimental site such that more variation in kochia control and biomass produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…Previous research has indicated that the combination of herbicide rotation and tank‐mixtures can delay the evolution of new HR weed biotypes (Beckie et al., 2019; Busi et al., 2019; Gage et al., 2019), and these are endorsed as best management practices in both nonintegrated and integrated weed management programs (Knezevic & Cassman, 2003; Norsworthy et al., 2012). Research on HR weed populations has also shown that tank‐mixtures with multiple effective SOAs can control GR weed biotypes, such as common ragweed (Barnes, Knezevic, Sikkema, Lindquist, & Jhala, 2017; Byker et al., 2018), waterhemp (Jhala, Sandell, Sarangi, Kruger, & Knezevic, 2017), horseweed (Chahal & Jhala, 2019), and kochia (Sbatella et al., 2019). Similarly, tank‐mixtures with multiple effective SOAs have been shown to control other HR weed biotypes, such as PPO‐inhibitor resistant Palmer amaranth (Schwartz‐Lazaro, Norsworthy, Scott, & Barber, 2017) or atrazine/hydroxyphenyl‐pyruvate‐dioxygenase inhibitor‒resistant Palmer amaranth (Chahal & Jhala, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has indicated that the combination of herbicide rotation and tank‐mixtures can delay the evolution of new HR weed biotypes (Beckie et al., 2019; Busi et al., 2019; Gage et al., 2019), and these are endorsed as best management practices in both nonintegrated and integrated weed management programs (Knezevic & Cassman, 2003; Norsworthy et al., 2012). Research on HR weed populations has also shown that tank‐mixtures with multiple effective SOAs can control GR weed biotypes, such as common ragweed (Barnes, Knezevic, Sikkema, Lindquist, & Jhala, 2017; Byker et al., 2018), waterhemp (Jhala, Sandell, Sarangi, Kruger, & Knezevic, 2017), horseweed (Chahal & Jhala, 2019), and kochia (Sbatella et al., 2019). Similarly, tank‐mixtures with multiple effective SOAs have been shown to control other HR weed biotypes, such as PPO‐inhibitor resistant Palmer amaranth (Schwartz‐Lazaro, Norsworthy, Scott, & Barber, 2017) or atrazine/hydroxyphenyl‐pyruvate‐dioxygenase inhibitor‒resistant Palmer amaranth (Chahal & Jhala, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Based on representative herbicide programs in the United States, GR kochia control varied among experimental sites to a greater extent in wheat compared with corn (Zea mays L.) or soybean [Glycine max (L.) Merr.] (Sbatella et al 2019). Lower densities of glyphosate-susceptible (GS) kochia (14 and 21 plants m -2 ) reduced spring wheat yield by 10 to 33% in Manitoba, while higher densities (195 to 520 plants m -2 ) reduced yield by 40 to 73% (Friesen et al 2009).…”
mentioning
confidence: 99%
“…Wicks et al (1994) documented 96% control of triazine-resistant kochia with paraquat applied as a burndown treatment prior to sorghum planting. Similarly, excellent control (>97%) of GR kochia has been reported with bromoxynil þ pyrasulfotole, bromoxynil þ fluroxypyr, paraquat, and saflufenacil alone or in combination with 2,4-D in two separate studies (Kumar et al 2014;Sbatella et al 2019). In the current study, glufosinate and a premix of 2,4-D þ bromoxynil þ fluroxypyr resulted in greater injury (96% vs. 84% averaged) to the KS-SUS than the KS-4H accession.…”
Section: Percent Visible Injurymentioning
confidence: 59%